2010
DOI: 10.1021/jm100612r
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Approach to the Discovery of Potent Inhibitors against Glycosyltransferases

Abstract: We describe a standardized approach for searching potent and selective inhibitors of glycosyltransferases by high throughput quantitative MALDI-TOFMS-based screening of focused compound libraries constructed by 1,3-dipolar cycloaddition of the desired azidosugar nucleotides with various alkynes. An aminooxy-functionalized reagent with a stable isotope was conjugated with oligosaccharides to afford glycopeptides as acceptor substrates with improved ion sensitivity. Enhanced ionization potency of new substrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 65 publications
0
35
0
Order By: Relevance
“…But the modification of Neu5Ac of CMP-Neu5Ac for seeking effective sialyltransferase inhibitors is worth exploring . Hosoguchi and co-workers reported that modification at C-5 position of CMP-Neu5Ac with bulky steroid analog (7) had strong impact to the catalytic action by sialyltransferases [26]. It showed that compound 7 is a highly promising inhibitor against α2,3-ST (ST3Gal III) (IC 50 = 8.2 μM).…”
Section: Cmp-sialic Acid Analogsmentioning
confidence: 99%
“…But the modification of Neu5Ac of CMP-Neu5Ac for seeking effective sialyltransferase inhibitors is worth exploring . Hosoguchi and co-workers reported that modification at C-5 position of CMP-Neu5Ac with bulky steroid analog (7) had strong impact to the catalytic action by sialyltransferases [26]. It showed that compound 7 is a highly promising inhibitor against α2,3-ST (ST3Gal III) (IC 50 = 8.2 μM).…”
Section: Cmp-sialic Acid Analogsmentioning
confidence: 99%
“…In 2011, the first two crystal structures of human OGT were solved: a binary complex with uridine 5'-diphosphate (UDP) and a ternary complex with UDP and a peptide substrate, including the catalytic region (PDB codes: 3PE3 and 3PE4) [536]. Additional reports discussing the mechanism underlining OGT and OGA activities as well as smallmolecule inhibitors and drug discovery methodologies have recently appeared [537][538][539][540][541][542][543]. Glycosyltransferases have been recently used to derive glycosylated analogues of novobiocin with improved activity against several cancer cell lines [544].…”
Section: Glycosylationmentioning
confidence: 99%
“…Plant-derived or synthetic inhibitors of the sialic acid machinery are rare and show low efficacy (9). The rational design of sialic acid analogues that interfere with the cellular sialic acid synthesis machinery might form a more promising approach (10)(11)(12). Here sialyltransferases constitute an attractive target as they have been shown to underlie aberrant cancer sialylation.…”
Section: Introductionmentioning
confidence: 99%